Acute Hemodynamic Effects of Simultaneous and Sequential Multi-Point Pacing in Heart Failure Patients With an Expected Higher Rate of Sub-response to Cardiac Resynchronization Therapy: Results of Multicenter SYNSEQ Study - Sterliński, Maciej; Zakrzewska-Koperska, Joanna; Maciąg, Aleksander; Sokal, Adam; Osca-Asensi, Joaquin; Wang, Lingwei; Spyropoulou, Vasiliki; Maus, Baerbel; Lemme, Francesca; Okafor, Osita; Stegemann, Berthold; Cornelussen, Richard; et al. (Frontiers in Cardiovascular Medicine, 2022)
The aim of the SYNSEQ (Left Ventricular Synchronous vs. Sequential MultiSpot Pacing for CRT) study was to evaluate the acute hemodynamic response (AHR) of simultaneous (3P-MPP syn) or sequential (3P-MPP seq) multi-3-point-left-ventricular (LV) pacing vs. single point pacing (SPP) in a group of patients at risk of a suboptimal response to cardiac resynchronization therapy (CRT). Twenty five patients with myocardial scar or QRS ≤ 150 or the absence of LBBB (age: 66 ± 12 years, QRS: 159 ± 12 ms, NYHA class II/III, LVEF ≤ 35%) underwent acute hemodynamic assessment by LV + dP/dtmax with a variety of LV pacing configurations at an optimized AV delay. The change in LV + dP/dt max (%ΔLV + dP/dt max) with 3P-MPP syn (15.6%, 95% CI: 8.8%-22.5%) was neither statistically significantly different to 3P-MPP seq (11.8%, 95% CI: 7.6-16.0%) nor to SPP basal (11.5%, 95% CI:7.1-15.9%) or SPP mid (12.2%, 95% CI:7.9-16.5%), but higher than SPP apical (10.6%, 95% CI:5.3-15.9%, p = 0.03). AHR (defined as a %ΔLV + dP/dt max ≥ 10%) varied between pacing configurations: 36% (9/25) for SPP apical, 44% (11/25) for SPP basal, 54% (13/24) for SPP mid, 56% (14/25) for 3P-MPP syn and 48% (11/23) for 3P-MPP seq.Fifteen patients (15/25, 60%) had an AHR in at least one pacing configuration. AHR was observed in 10/13 (77%) patients with a LBBB but only in 5/12 (42%) patients with a non-LBBB (p = 0.11). To conclude, simultaneous or sequential multipoint pacing compared to single point pacing did not improve the acute hemodynamic effect in a suboptimal CRT response population. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT02914457.